Electrochemical Oxidation of Glycine with Bimetallic Nickel−Manganese Oxide Catalysts. Issue 2 (17th January 2020) - Mohan, Roopathy; Modak, Arindam; Subramanian, Palaniappan; Cahan, Rivka; Sivakumar, P.; Gedanken, Aharon; Schechter, Alex
Abstract: A simple template‐free hydrothermal route followed by high‐temperature (800 °C) annealing in air forms Ni–Mn bimetallic oxides, namely NiMn2 O4, Ni1.5 Mn1.5 O4, and MnNi2 O4, which are characterized by XRD, Raman, EDS, and SEM analysis. The electrocatalytic activity of these metal oxides toward the oxidation of glycine molecules in alkaline condition was studied by cyclic voltammetry and linear sweep voltammetry methods. Among other nickel manganese bimetallic oxides and monometallic oxides (Mn2 O3, NiO), Ni1.5 Mn1.5 O4 shows excellent redox characteristics with high oxidation current density (310 μA cm −2 at 0.43 V vs. Ag/AgCl) and lower onset potential (0.22 V vs. Ag/AgCl). Additionally, Ni1.5 Mn1.5 O4 exhibits a moderate Tafel slope (78 mV dec −1 ) and is electrochemically stable, as confirmed from chronoamperometry, indicating its potential for glycine oxidation. The linear dependence of the oxidation current with glycine concentration signifies that the overall process is diffusion controlled. The electrochemical results suggest that bimetallic mixed Mn and Ni oxides are promising glycine oxidation catalysts, which may be attributed to the cooperative effect between different Ni and Mn elements. Abstract : Mix it up : The nickel manganese oxide spinel nanostructure shows a higher activity of glycine electrooxidation in alkaline electrolytes than pure nickel oxide and manganese oxide.